15x+(-6x+5)-2-(-x+3)=(7x+23)-x+(3-2x)

Simple and best practice solution for 15x+(-6x+5)-2-(-x+3)=(7x+23)-x+(3-2x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 15x+(-6x+5)-2-(-x+3)=(7x+23)-x+(3-2x) equation:


15x+(-6x+5)-2-(-x+3)=(7x+23)-x+(3-2x)

We simplify the equation to the form, which is simple to understand
15x+(-6x+5)-2-(-x+3)=(7x+23)-x+(3-2x)

Remove unnecessary parentheses
+15x-6x+5-2-(-x+3+)=+(+7x+23+)-x+(+3-2x+)

Remove unnecessary parentheses
15x-6x+5-2+1x-3=(7x+23)-x+(3-2x)

Remove unnecessary parentheses
15x-6x+5-2+1x-3=7x+23-x+(3-2x)

Remove unnecessary parentheses
+15x-6x+5-2+1x-3=+7x+23-x+3-2x

We move all terms containing x to the left and all other terms to the right.
+15x-6x+1x-7x+1x+2x=+23+3-5+2+3

We simplify left and right side of the equation.
+6x=+26

We divide both sides of the equation by 6 to get x.
x=4.33333333333

See similar equations:

| -8v=64 | | 9b+4.8=17.4 | | x-5/8 | | 2x+2x+4x-1+4x-1=68 | | 12x=-216 | | 16=k/2-7 | | W-895=-54 | | 50=16g+2 | | 4x+-2y=38 | | -p/7=-9 | | 2n^2+3n=0 | | 6+(12/6)/2 | | 2/3t=-10 | | -91=7p | | 2a-1=-(a+4) | | 24+9n=-3 | | 12x^2=18x-1 | | 5(m+3)+7m=3(m-9) | | 5(-7x+2)=-40 | | 3(3n+40)=54+6n | | 24=8c | | -3x-15=9x+9 | | m+4=1 | | 2x^2+3-5=0 | | 6p=-96 | | n/8=-12 | | 30=12n-18 | | -5+n=-23 | | -632=4g | | -9j-10=62 | | 8=-12+x | | 2=4h-14 |

Equations solver categories